(untitled) (Research, Society and Development, 2020)
The objective of this article is to understand the new teaching-learning alternatives through digital platforms Google Classroom and Google Meet at the Federal Institute of Maranhão de Coelho Neto to students of the 3rd year of high School during the pandemic period in Brazil. They are playing an important pedagogical role in innovation for students who have felt the impacts of the closure of educational institutions, especially those from the public sphere who were the most affected when it comes to the technological area. To this end, we will use as theoretical input as Moore’s reflections for whom the dialogue in an educational relationship is directed towards the progress of understanding by the student; Pereira who understands the virtual learning environment as an option to mediate teaching and learning; Mendes and Lemes who observe some gaps between the face-to-face classes and the pedagogical proposals in the area of ​​technology.